Balancing Regulatory Efficiency and Halal Integrity:A Governance Analysis of Indonesia's Self-Declaration System in Halal Certification - A. Sahhari, Abdulrahman Salman; Azmi, Lalu Khairil; Razi, Raffy Fachrul; Mukti, Kafi Wsuwesta; Hidayatullah, Imam (Graduate School of UIN Syarif Hidayatullah Jakarta, 2025)
Indonesia’s halal certification self-declaration system faces criticism for oversight and accountability gaps. This study evaluates its compliance with transparency principles under national law and Islamic jurisprudence (fatwa), employing a mixed-methods analysis of legislative texts, case studies, and interviews. Contrasting law in books and law in action, findings reveal systemic gaps between regulatory ideals and implementation. Procedural misconduct—including data falsification and lax verification by Halal Product Process (PPH) officers—undermines accountability, exposing flaws in coordination and audit mechanisms. The self-declaration model inadequately safeguards halal integrity, requiring reforms: real-time monitoring, standardized verification protocols, and collaborative governance between Indonesia’s National Ulama Council (MUI) and state agencies. Such measures are vital to aligning Indonesia’s halal assurance with global Islamic economy benchmarks while safeguarding consumer trust and principles. The study underscores bridging normative-practical divides through adaptive governance, ensuring coherence and compliance in Indonesia’s evolving halal ecosystem.